The effect of fixed capital formation rate on gross domestic product in Iraq - Sameer Siham Dawood; Bilal Kadhim Haidar; Mohammad Ghazi Nussaif Jasim (Public and Municipal Finance)
The total fixed capital formation is one of the main and influential determinants of production function through its impact on production costs, competitiveness, and profits. The Iraqi gross domestic product depends on one sector (the oil sector) in financing the government budget, which may lead to crises in case of oil price collapse. Therefore, the study aims to clarify the imbalance in the production function and the real output of the Iraqi economy and to indicate the role of the total fixed capital formation in this imbalance. The econometric methods were used to measure the degree of influence of the total fixed capital formation (independent variable) on the gross domestic product (dependent variable) from 2004 to 2020. The results showed a robust relationship between fixed capital formation and gross domestic product, where the independent variable affects the dependent variable by 4.5%, while the oil sector dominated the total value added by its acquisition of the total fixed capital formation by 47.45%, and the productive sectors of agriculture and industry achieved value added of 3.8%. The study concluded that the distribution of total capital formation by sector has an impact on the gross domestic product. Therefore, it is necessary to distribute the total fixed capital formation to the productive and production-supporting sectors to achieve economic growth and diversify the structure of the gross domestic product.